Bridging Needs and Expectations of Individuals With Physical Disabilities and Community Services Stakeholders for the Cocreation of an Adapted Physical Activity Platform in Virtual Reality: Qualitative Study - Aurélien Ramos; Maxence Boisvert; Elodie Traverse; Danielle Levac; Martin Lemay; Marika Demers; Martine Bordeleau; Sarah-Maude Ruest; Roxanne Périnet-Lacroix; Krista L Best; Maxime T Robert (JMIR Serious Games)
Abstract BackgroundPhysical activity supports the health and well-being of individuals with physical disabilities. Despite the significance of engaging in physical activity, barriers faced by individuals with disabilities, such as limited access to adapted facilities and lack of transportation, can restrict their participation. Community organizations play a role in addressing these challenges, but virtual reality (VR) also offers a way to diversify adapted activities. In some situations, VR can help overcome the resource limitations of organizations by providing accessible, engaging, and highly personalized options for physical activity. ObjectiveThe aim of this study was to explore the needs and expectations of individuals with physical disabilities and their interventionists for the use of a VR physical activity platform in a community organization. MethodsA descriptive qualitative study was conducted using semistructured interviews with individuals with physical disabilities and their interventionists, all associated with a nonprofit organization promoting physical activity among people with disabilities. Data were analyzed using an inductive thematic approach. ResultsIn total, 15 participants, including 8 people with physical disabilities and 7 interventionists, were interviewed. Through this discussion, we gained insights into the everyday challenges faced by individuals with disabilities and identified priorities for community organizations. Subsequently, we discussed key considerations for using VR, including adapting activities, the possibility of fostering a more positive perception of physical activity, and harnessing the potential of VR to improve access to physical activity. We also discussed the importance of supporting personal goals and creating inclusive experiences while recognizing challenges such as technical difficulties and connectivity issues. ConclusionsBy exploring the needs and expectations regarding VR technology from individuals with physical disabilities and their interventionists, this study provided essential insights for integrating immersive and nonimmersive VR into community organizations, informing next steps for the design of adapted physical activities in VR.